Optimalisasi Kinerja Dosen Berbasis Quality Of Work Life - Nindya Faradiba; Adya Hermawati; Soedjono Soedjono (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of Quality of Work Life on Lecturer Performance through strengthening Organizational Commitment. The population in this study were all lecturers working at Insitut Teknologi Sains dan Kesehatan RS dr. Soepraoen Malang. The sampling technique used in this study is Nonprobability Sampling with a total of 71 respondents and the data is processed through Smart Partial Least Square (PLS) software. The results of this study indicate that the better the Quality of Work Life, the more it will contribute to the lecturer performance of Insitut Teknologi Sains dan Kesehatan RS dr. Soepraoen Malang. Likewise with the Quality of Work Life which is getting better it will contribute to the organizational commitment of lecturers. It was also found in this study that organizational commitment which was still low could not contribute to improving the lecturer performance of Insitut Teknologi Sains dan Kesehatan RS dr. Soepraoen Malang. And organizational commitment has not been able to play a role in mediating the relationship between Quality of Work Life and lecturer performance of Insitut Teknologi Sains dan Kesehatan RS dr. Soepraoen Malang.